Peningkatkan Pemahaman Konsep Fisika Melalui Penerapan Model Problem Based Learning Berbantu LKPD - Muhammad Taufik Sibagariang; Almira Amir; Yenni Khairani Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This study was conducted to improve the understanding of physics concepts of grade XI-7 students of SMA Negeri 2 Sibolga through the application of the problem based learning (PBL) learning model supported by the use of student waorksheets (LKPD) on static flui material. This study applied th classroom action research (CAR) method which was carried out in two cycles. Each cycle consisted of the stage of planning, action implementation, observation sheets and test to measure conceptual understanding. The results of the study showed a gradual increase in the level of learning completion, namely from 13% in the pre-cycle I, 61.29% in the first meeting of cycle II, and reaching 82% in the second meeting of cycle II with an average value above 75. This finding proves that the use of the PBL model assisted by LKPD is able to significantly increase student’s activeness, involvement, and understanding of physics concepts when compared to conventional learning